Toleransi Digital dan Moderasi Beragama Generasi Z di Indonesia: Analisis Negosiasi Nilai di Ruang Publik Media Sosial - Masrur, Muhamad; Zulfa, Indah Naela; Afna, Inda Millata; Putri, Norma Kartika; Hasanah, Nur Lailatul (Moderasi : Journal of Islamic Studies, 2025)
This study aims to examine the dynamics of social interaction among Generation Z in the digital sphere and to identify the factors influencing the formation of tolerance and religious moderation attitudes on social media. The research focuses on how Generation Z negotiates identity, values, and empathy within the digital public sphere shaped by algorithms and opinion polarization. A descriptive qualitative approach was employed, combining discourse analysis of interfaith-themed TikTok content such as “Edis TV Batu Hajar Aswad” and “Habib Jafar Kumpul Enam Agama” with reflective questionnaires from five Generation Z respondents. Data were analyzed using Miles and Huberman’s interactive model through the stages of data reduction, display, and verification, supported by source and method triangulation to ensure validity. The findings reveal that social media functions as a site for social learning and interfaith identity expression, where digital tolerance values are developed through interfaith meaning negotiation, digital empathy practices, and reflection on algorithmic bias. The formation of tolerant attitudes is influenced by family values, multicultural education, reflective digital literacy, and algorithmic exposure. The study highlights the significance of wasathiyah the Islamic principle of balance and justice as a moral foundation for fostering digital religious moderation and empathy-based literacy to strengthen social cohesion and a culture of tolerance in Indonesia’s multicultural society.